Application of Novel Terminal Technologies for Superjunction Power MOSFETs. Issue 4 (4th July 2018) - Cao, Zhen; Duan, Baoxing; Shi, Tongtong; Yuan, Song; Yang, Yintang
ABSTRACT: In this technical review, several superjunction (SJ) power MOSFETs based on the novel terminal technologies have been discussed. The electric field distributions of these SJ MOSFETs are optimized with superior performance. Thanks to the new terminal technologies, the trade-off between the breakdown voltage (BV) and the specific on-resistance ( R on, sp ) of these devices are effectively improved. Physical mechanisms of the new terminal technologies are analysed, and the trade-offs of these SJ MOSFETs are compared in detail.